Climate change concerns and mortgage lending - DUAN, Tinghua (Institutional Knowledge at Singapore Management University, 2024)
We examine whether beliefs about climate change affect loan officers’ mortgage lending decisions. We show that abnormally high local temperature leads to elevated attention to and belief in climate change in a region. Loan officers approve fewer mortgage applications and originate lower amounts of loans in abnormally warm weather. This effect is stronger among counties heavily exposed to the risk of sea-level rise, during periods of heightened public attention to climate change, and for loans originated by small lenders. Additional tests suggest that the negative relation between temperature and approval rate is not fully explained by changes in local economic conditions and demand for mortgage credit, or deteriorating quality of loan applicants. By contrast, Fintech lenders partially fill the gap in demand left by traditional lenders when local temperature is abnormally high.